Surface Modification of Electrospun PAN Nanofibers and Its Application for Adsorption of Lead Ions (Journal of Fiber Bioengineering and Informatics, 2018)
Surface modified PAN nanofibers were prepared by reaction between PAN electrospun nanofibers andhydroxylamine hydrochloride. The prepared nanofibers were used as matrix for lead ions adsorption.Micrographs of modified normal PAN fibers and PAN nanofibers were observed by Field EmissionScanning Electron Microscope (FESEM), and Fourier Transform Spectroscopy (FTIR) spectra of thesurface modified PAN nanofibers were recorded. The adsorption capacity of modfied PAN nanofibersand modified normal PAN fibers were calculated, and the adsorption isotherm of Pb^{2+} on the modifiedPAN nanofibers was studied. According to the results of experiment, surface modified PAN nanofibershad excellent adsorption capacity for lead ions.